2014
DOI: 10.1128/iai.01514-14
|View full text |Cite
|
Sign up to set email alerts
|

Dose Response of Listeria monocytogenes Invasion, Fetal Morbidity, and Fetal Mortality after Oral Challenge in Pregnant and Nonpregnant Mongolian Gerbils

Abstract: Listeria monocytogenes is a food-borne pathogen that can result in adverse pregnancy outcomes, such as stillbirth or premature delivery. The Mongolian gerbil was recently proposed as the most appropriate small-animal model of listeriosis due to its susceptibility to the same invasion pathways as humans. The objectives of this study were to investigate invasion and adverse pregnancy outcomes in gerbils orally exposed to L. monocytogenes, to compare the dose-response data to those of other animal models, and to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…Even though Mongolian gerbils are akin to humans in their permissiveness to InlA and InlB pathways, fetal deaths were observed only in the highest (10 9 CFU) treatment group in pregnant gerbils, so that a dose response for fetal mortality could not be calculated (Disson et al, ; Roulo et al, ). These results show that gerbils are less sensitive than guinea pigs and nonhuman primates to listeriosis, and, thus, may not be an appropriate model to study human listeriosis during pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Even though Mongolian gerbils are akin to humans in their permissiveness to InlA and InlB pathways, fetal deaths were observed only in the highest (10 9 CFU) treatment group in pregnant gerbils, so that a dose response for fetal mortality could not be calculated (Disson et al, ; Roulo et al, ). These results show that gerbils are less sensitive than guinea pigs and nonhuman primates to listeriosis, and, thus, may not be an appropriate model to study human listeriosis during pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…There are however drawbacks when using the gerbil model: The genome sequence of gerbils has not yet been published and they are not yet as commercially available as mice. Also, despite having functional InlA and InlB pathways, it was recently shown that very high doses of Listeria (~1 × 10 9 ) were required to cause stillbirth in gerbils (Roulo et al, 2014 ).…”
Section: Animal Model Systems For Studying Listeria Pathogenicitymentioning
confidence: 99%
“…LLO is a crucial virulence factor in the pathogenesis of Listeria, and the deletion of LLO can significantly inhibit bacterial escape from the phagosome and reduce the pathogenicity of the bacteria [10,11], which suggests that LLO deletion could be regarded as an important and effective target in the therapy of Listeria infections. In addition, the severe inflammatory response caused by Listeria infection also causes harm to the infected host and particularly induces a risk for abortion in pregnant women [34], which indicates that attenuating the inflammatory response could be an important strategy for the treatment of Listeria infection.…”
Section: Discussionmentioning
confidence: 99%